Audit committees and financial reporting quality in Singapore - Yuanto KUSNADI, (Institutional Knowledge at Singapore Management University, 2016)
We examine three characteristics (independence, expertise, and overlapping membership) of audit committees and their impact on the financial reporting quality for Singapore-listed companies. The main finding is that financial reporting quality will be higher if audit committees have mixed expertise in accounting, finance, and/or supervisory. In addition, we do not find evidence that incremental independence of audit committees enhances financial reporting quality because audit committees already consist of a majority of independent directors. Finally, we fail to find any impact of overlapping membership on audit and remuneration committees on financial reporting quality. Overall, the results have policy implications on improving corporate governance effectiveness in terms of financial reporting quality.